Effect of Controlled Fermentation on Proximate Composition of Cocoa Bean (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
The source of microorganisms used during fermentation is very important to the output of the fermentation process. The use of naturally predominant species from a fermentation process gives rise to improved fermentation than the use of microorganisms from culture collections. Natural and controlled fermentation of the cocoa bean inoculated with defined starter consortia of Acetobacter pasteurianus, Saccharomyces cerevisiae and Lactobacillus plantarum was done. Cocoa fermentation was carried out under two experimental conditions; beans naturally fermented with micro flora naturally present on the substrate and beans inoculated with a defined cocktail containing defined starters from a batch of previously fermented cocoa beans at different time course. The dynamics in microbial population and time course were determined by microbial count method. The chemical content of naturally fermented and controlled fermented cocoa beans were determined through proximate analysis respectively. The dynamics in microbial composition showed that the yeast, acetic acid bacteria and acetic acid bacteria populations increased slowly and reached maximum of 6.1 x 107, 4.4x 107 and 5.4x 107cfu\ml respectively, at days 3-4 for the natural fermentation, while they increased abruptly and reached maximum of 7.2x 107, 6.0x 107 and 6.1x 107cfu\ml respectively at day 2-3 for the controlled fermentation. Starter culture addition resulted in significant (P
Keywords: Controlled fermentation; Natural fermentation; Proximate analysis; Starter cultures